The Thirty Years War : Europe's tragedy - Wilson, Peter H. (Peter Hamish) (Cambridge, Mass. : Belknap Press of Harvard University Press, 2009)
A deadly continental struggle, the Thirty Years War devastated seventeenth-century Europe, killing nearly a quarter of all Germans and laying waste to towns and countryside alike. In a major reassessment, Wilson argues that religion was not the catalyst, but one element in a lethal stew of political, social, and dynastic forces that fed the conflict--a conflict that ultimately transformed the map of the modern world
A deadly continental struggle, the Thirty Years War devastated seventeenth-century Europe, killing nearly a quarter of all Germans and laying waste to towns and countryside alike. In a major reassessment, Wilson argues that religion was not the catalyst, but one element in a lethal stew of political, social, and dynastic forces that fed the conflict--a conflict that ultimately transformed the map of the modern world
Introduction -- Trouble in the heart of Christendom -- Casa d'Austria -- The Turkish War and its consequences -- Pax Hispanica -- Dominium Maris Baltici -- From Rudolf to Matthias 1582-1612 -- On the brink? -- The Bohemian revolt 1618-20 -- Ferdinand triumphant 1621-4 -- Olivares and Richelieu -- Denmark's war against the emperor 1625-9 -- The threat of European war 1628-30 -- The lion of the north 1630-2 -- Without Gustavus 1633-4 -- For the liberty of Germany 1635-6 -- Habsburg high tide 1637-40 -- In the balance 1641-3 -- Pressure to negotiate 1644-5 -- War or peace 1646-8 -- The Westphalian settlement -- The human and material cost -- Experiencing war
Includes bibliographical references and index
Keywords: Thirty Years' War, 1618-1648; Europe -- History, Military -- 1492-1648